2018
DOI: 10.1002/pssa.201700754
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Reversible Optical Properties of Hydrogenated Amorphous Silicon: A Promising Optically Programmable Photonic Material

Abstract: Reversible optical properties (refractive index, n, and extinction coefficient, k) upon light soaking and annealing are predicted to originate from the metastable properties of hydrogenated amorphous silicon (a-Si:H). Optically programmable photonic devices can be demonstrated when a-Si:H is established as a potential programmable photonic material. Therefore, the effects of prolonged high intensity light soaking and annealing are investigated. A set of a-Si:H films is deposited by inductively coupled plasma-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…It can be concluded that the surface of the a‐Si:H oxidized and saturated over time considering the reference sample (Figure S4a–d,b–e, Supporting Information). The sample that went through annealing and light soaking showed a higher oxidized state that can be related to high‐intensity light‐induced oxidation when compared to the reference sample . In addition, the reference sample going through surface oxidation over time also corroborates the observation made in Figure a, with the measured spontaneous blue‐shift over the aging period after first annealing step when the AR coating was left in ambient conditions (Figure S4d,e, Supporting Information).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…It can be concluded that the surface of the a‐Si:H oxidized and saturated over time considering the reference sample (Figure S4a–d,b–e, Supporting Information). The sample that went through annealing and light soaking showed a higher oxidized state that can be related to high‐intensity light‐induced oxidation when compared to the reference sample . In addition, the reference sample going through surface oxidation over time also corroborates the observation made in Figure a, with the measured spontaneous blue‐shift over the aging period after first annealing step when the AR coating was left in ambient conditions (Figure S4d,e, Supporting Information).…”
Section: Resultssupporting
confidence: 79%
“…The sample that went through annealing and light soaking showed a higher oxidized state that can be related to high-intensity light-induced oxidation when compared to the reference sample. [29] In addition, the reference sample going through surface oxidation over time also corroborates the observation made in Figure 2a, with the measured spontaneous blue-shift over the aging period after first annealing step when the AR coating was left in ambient conditions ( Figure S4d,e, Supporting Information). Therefore, it can be concluded that the Si-O related FTIR and XPS measurements corroborate the surface oxidation.…”
Section: Thin-film Interferometrysupporting
confidence: 84%
See 3 more Smart Citations